2013
DOI: 10.1007/s10911-013-9273-9
|View full text |Cite
|
Sign up to set email alerts
|

Metals and Breast Cancer

Abstract: Metalloestrogens are metals that activate the estrogen receptor in the absence of estradiol. The metalloestrogens fall into two subclasses: metal/metalloid anions and bivalent cationic metals. The metal/metalloid anions include compounds such as arsenite, nitrite, selenite, and vanadate while the bivalent cations include metals such as cadmium, calcium, cobalt, copper, nickel, chromium, lead, mercury, and tin. The best studied metalloestrogen is cadmium. It is a heavy metal and a prevalent environmental contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 94 publications
2
122
0
4
Order By: Relevance
“…In the general population, the primary sources of cadmium are cigarette smoke, food, water, and ambient air (Jarup 2003). Cadmium is easily absorbed by crops and vegetables, such as rice, wheat, and potatoes, and can reach high concentrations in shellfish, offal, and certain seeds (Akesson et al 2014), and, to a lesser degree, drinking water (Byrne et al 2013). It was suggested that approximately 75 % of the total dietary cadmium intake is from vegetable foods with the highest contribution from cereals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population, the primary sources of cadmium are cigarette smoke, food, water, and ambient air (Jarup 2003). Cadmium is easily absorbed by crops and vegetables, such as rice, wheat, and potatoes, and can reach high concentrations in shellfish, offal, and certain seeds (Akesson et al 2014), and, to a lesser degree, drinking water (Byrne et al 2013). It was suggested that approximately 75 % of the total dietary cadmium intake is from vegetable foods with the highest contribution from cereals.…”
Section: Discussionmentioning
confidence: 99%
“…Exposures to cadmium and cadmium compounds occur primarily in workplaces-mining, smelting, processing, product formulations, and battery manufacturing-whereas non-occupational exposures come from various foods and tobacco smoking. With respect to the general population, cigarette smoke is also an important source of human chronic exposure to cadmium, which is effectively absorbed in the lungs, and about 2 to 4 μg cadmium is absorbed from one pack of cigarettes per day (Byrne et al 2013). Except for smokers, relevant chronic exposure occurs due to dietary intake.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial contamination, mostly the byproduct of smelters, is the primary source of cadmium in environment. With respect to the general population, except for smokers, relevant chronic exposure occurs due to dietary intake, for cadmium, is easily absorbed by crops and vegetables, such as rice, wheat, and potatoes and can reach high concentrations in shellfish, offal, and certain seeds (Åkesson et al 2014) and, to a lesser degree, drinking water (Byrne et al 2013). It has been estimated that in a pollution-free environment, daily intake of cadmium in food is about 8 to 25 μg/day (Gallagher et al 2010;Satarug et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that in a pollution-free environment, daily intake of cadmium in food is about 8 to 25 μg/day (Gallagher et al 2010;Satarug et al 2010). Cigarette smoke is also an important source of human chronic exposure to cadmium, which is effectively absorbed in the lungs, and about 2 to 4 μg cadmium is absorbed from one pack of cigarettes per day (Byrne et al 2013). With long biological half-life, about 10-30 years (IARC 1976), whole blood concentration of cadmium is a valid marker of recent and long-term exposure (Åkesson et al 2014;Jarup et al 1998), providing a means for assessing total body burden of cadmium.…”
Section: Introductionmentioning
confidence: 99%
“…They include metals such as cadmium, calcium, cobalt, copper, nickel, chromium, lead, mercury and tin [196]. Divalent metals and metal anions activate ER-α through the formation of a complex within the hormone-binding domain of the receptor [197].…”
Section: Metalsmentioning
confidence: 99%